Quantification of β-1,3-D-glucan in two wild edible mushrooms of Andhra Pradesh - Sai, Isha; Basavaraju, R (Mushroom Research, 2020)
Mushroom derived β-glucan polysaccharides are known for their activity as immunomodulators and anti-carcinogenic agents. In the present work, specific colorimetric method for β-1,3-D-glucan quantification was used. This method is based on interaction of a triple helix tertiary structure of β-1,3-D-glucan with Congo red dye and was detected by bathochromic shift from 488 to 512nm (>20nm)in UV-VIS spectrophotometer. Two different methods (method-1 and method-2) were used to extract the polysaccharide in various fractions of mushroom samples. The results showed that the total β- 1,3-D-glucan content was found to be more in both the mushrooms using extraction method-2. Termitomyces heimii was found to possess high amount of total β-1,3-D-glucan (43.55mg/g dry weight) compared to Podaxis pistillaris (9.89mg/g dry weight).